The Influence of Open Innovation and Digital Literacy on Business Sustainability with New Product Development as an Intervening Variable in Leading UMKM in Buleleng District - Srikarsa, Nyoman; Gorda, A.A.N. Eddy Supriyadinatha; Pasek, Gede Widiadnyana (Universitas Pendidikan Ganesha, 2024)
The aim of this research is to assist UMKM (Micro, Small, and Medium Enterprises) in gaining a competitive advantage by focusing on key factors such as Open Innovation, New Product Development (NPD), and Digital Literacy in their marketing strategies. This study was conducted in Buleleng Regency, Bali, with a sample of 60 UMKM businesses. The research used questionnaires as the primary data collection technique, and the data was analyzed using Structural Equation Modeling (SEM) to assess the relationships between the variables. The results of the study indicate that Open Innovation, Digital Literacy, and New Product Development significantly influence the sustainability of UMKM businesses in the region. Open innovation, which involves utilizing both internal and external ideas, helps businesses enhance their product offerings and adapt to changing market conditions. Digital literacy enables UMKM to leverage digital platforms for marketing and customer engagement, while new product development ensures that businesses can meet evolving customer needs and stay competitive. The findings have critical implications for Marketing Management, suggesting that UMKM should prioritize innovation and digital capabilities to improve their marketing strategies. By doing so, they can enhance their market position, improve customer satisfaction, and ultimately achieve long-term business sustainability. This research provides valuable insights for UMKM to adapt to the modern market landscape and create more effective strategies to thrive in a competitive environment.